Hertzian testing of ceramics - Roberts, S (1999)
The paper reviews recent work on the fracture mechanics of ring crack formation, from pre-existing small surface cracks, when a hard sphere is pressed elastically against a hard surface. It summarises the ways in which data from these 'Hertzian' tests may be used to determine the extent of surface cracking damage, the materials fracture toughness, and the strength of any residual stress in the surface. Examples are given of experiments applying these test methods.